An exploration of children's views of bed-wetting at 9 years. - Butler R; Heron J (Child: Care, Health & Development, 2008)
Background Although some empirical investigations have explored the impact of nocturnal enuresis for sufferers, little is known about how children in general understand nocturnal enuresis. This study employed a large cohort of children at 9 years, asking directly about the perceived difficulty of bed-wetting in relation to an extensive range of life events. Method The sample comprised 8209 children, 4012 (48.9%) male and 4197 (51.1%) female who, as part of the Avon Longitudinal Study of Parents and Children survey, completed a booklet called 'My World' which included a section of 21 items concerned with childhood difficulties. Results Bed-wetting was highly endorsed as a difficulty for children, and factor analysis revealed it to be construed as a social problem. Girls were more likely to consider events of a social and emotional nature to be difficult, whereas boys rated antisocial events as more problematic. Boys and those who suffer from nocturnal enuresis were significantly more likely to view bed-wetting as more difficult for children. Conclusion Bed-wetting, which is construed as a social issue, tends to be rated as a major difficulty for children, increasingly so for boys and those who suffer from nocturnal enuresis.